Solvent-free sonochemical kabachnic-fields reaction to synthesize some new α-aminophosphonates catalyzed by nano-BF3SiO2. (3rd June 2018) - Ravikumar, D.; Mohan, S.; Subramanyam, Ch.; Rao, K. Prasada
GRAPHICAL ABSTRACT: ABSTRACT: To obtain a rapid, efficient synthesis of some new α-aminophosphonates, ultrasonic irradiation has been applied to the reaction mixtures containing amine, aromatic or heteroaromatic aldehydes and triethyl phosphite. The Kabachnik-Fields reaction was performed by using nano-BF3 SiO2 as a recyclable catalyst under solvent free conditions. Key advantages of this procedure consist in the eco-friendly and highly efficient reaction conditions, high yields, an easy work-up procedure, short reaction times and solvent free conditions. All title compounds were characterized by spectral and elemental analysis. They were further screened for their in vitro antioxidant activity by the DPPH, O 2− and NO methods. The majority of the title compounds showed good antioxidant activity when compared with the standard antioxidants.